Cardioprotection with halogenated gases: how does it occur? - Guerrero-Orriach JL; Escalona Belmonte JJ; Ramirez Fernandez A; Ramirez Aliaga M; Rubio Navarro M; Cruz Mañas J (Dove Medical Press, 2017)
Jose Luis Guerrero-Orriach,1–3 Juan Jose Escalona Belmonte,1 Alicia Ramirez Fernandez,1 Marta Ramirez Aliaga,1 Manuel Rubio Navarro,1 Jose Cruz Mañas1 1Department of Cardioanesthesiology, Virgen de la Victoria University Hospital, 2Instituto de Investigación Biomédica de Málaga (IBIMA), 3Department of Pharmacology and Pediatrics, University of Malaga, Malaga, Spain Abstract: Numerous studies have studied the effect of halogenated agents on the myocardium, highlighting the beneficial cardiac effect of the pharmacological mechanism (preconditioning and postconditioning) when employed before and after ischemia in patients with ischemic heart disease. Anesthetic preconditioning is related to the dose-dependent signal, while the degree of protection is related to the concentration of the administered drug and the duration of the administration itself. Triggers for postconditioning and preconditioning might have numerous pathways in common; mitochondrial protection and a decrease in inflammatory mediators could be the major biochemical elements. Several pathways have been identified, including attenuation of NFκB activation and reduced expression of TNFα, IL-1, intracellular adhesion molecules, eNOS, the hypercontraction reduction that follows reperfusion, and antiapoptotic activating kinases (Akt, ERK1/2). It appears that the preconditioning and postconditioning triggers have numerous similar paths. The key biochemical elements are protection of the mitochondria and reduction in inflammatory mediators, both of which are developed in various ways. We have studied this issue, and have published several articles on cardioprotection with halogenated gases. Our results confirm greater cardioprotection through myocardial preconditioning in patients anesthetized with sevoflurane compared with propofol, with decreasing levels of troponin and N-terminal brain natriuretic peptide prohormone. The difference between our studies and previous studies lies in the use of sedation with sevoflurane in the postoperative period. The results could be related to a prolonged effect, in addition to preconditioning and postconditioning, which could enhance the cardioprotective effect of sevoflurane in the postoperative period. With this review, we aim to clarify the importance of various mechanisms involved in preconditioning and postconditioning with halogenated gases, as supported by our studies. Keywords: sevoflurane, preconditioning, postconditioning, mechanisms, enzyme